1991
DOI: 10.1104/pp.97.4.1422
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Catalase Heme and Apoprotein Moieties in Cotyledons of Sunflower Seedlings

Abstract: The turnover of catalase apoprotein and catalase heme was studied in cotyledons of sunflower (Helianthus annuus L.) seedlings by density labeling of apoprotein and radioactive labeling of heme moieties. The heavy isotope (50% 2H20) and the radioactive isotope ([14C]5-aminolevulinic acid) were applied either during growth in the dark (day 0-2.5) or in the light (day 2.5 and 5). Following isopycnic centrifugation of catalase purified from cotyledons of 5-day-old seedlings, superimposition curve fitting was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…1D) could explain the persistent stimulation of antioxidant and detoxification genes in vitiligo melanocytes, whereas attenuated protein expression could be directly caused by altered intracellular redox balance affecting enzymes stability. In fact, it has been demonstrated that acceleration of catalase degradation caused by H 2 O 2 determines the increase of the corresponding gene transcription, producing a constant stady-state level of protein expression [27]. Activation of antioxidant gene expression indicated a compromised redox homeostasis in melanocytes isolated from vitiligo patients.…”
Section: Resultsmentioning
confidence: 99%
“…1D) could explain the persistent stimulation of antioxidant and detoxification genes in vitiligo melanocytes, whereas attenuated protein expression could be directly caused by altered intracellular redox balance affecting enzymes stability. In fact, it has been demonstrated that acceleration of catalase degradation caused by H 2 O 2 determines the increase of the corresponding gene transcription, producing a constant stady-state level of protein expression [27]. Activation of antioxidant gene expression indicated a compromised redox homeostasis in melanocytes isolated from vitiligo patients.…”
Section: Resultsmentioning
confidence: 99%
“…This interaction is also shown to inhibit catalase tetramerization, suggesting tetramerization of catalase is a peroxisomal event(45,48). However, several other reports suggest that cytosolic assembly of catalase can occur independent of peroxisomes (15,49,50). Four amino acids on the N-terminal end of Candida Tropicalis catalase are shown to regulate tetramerization of the protein(51).…”
Section: Discussionmentioning
confidence: 96%
“…In rat liver apo-catalase is present in 3 fold excess (1.6% compared to 0.5%) of holo-monomeric catalase (13). Lack of heme can increase the pool of apo-catalase and may promote its turnover (14,15). Exposure to oxidative stress can inactivate catalase (16-19), but whether this affects its structure is not completely understood.…”
Section: Introductionmentioning
confidence: 99%